The Effectiveness Of EM4 And Water Hyacinth Powder to Pprocess tofu liquid waste into liquid fertilizer for The Growth Biomass Azolla microphylla - Fitrianis Yulanda1; Budijono '; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Liquid wastes originated from tofu industries are rich in organic materials and it is potencial as basic materials for liquid fertilizer. To process the waste into liquid fertilizer, however, addition of EM4 and water hyacinth powder as N, P and K sources is needed. To understand the effectiveness of addition of water hyacinth powder in increasing the N, P and K content in the liquid waste, a study has been conducted on February to March 2015. Treatments applied were different concentration of water hyacinth powder. In 10 L of tofu liquid waste, there was 10 ml of EM4 and 24 gr (P1); 72 gr (P2); 120 gr (P3); 168 gr (P4) and 216 gr (P5) water hyacinth powder were added. The waste was fermented for 12 days and the N, P and K were analyzed. The quality of the fertilizer was tested by using it for fertilizing Azolla microphylla. Results shown that the highest N content was in the P3 (10,290.48 mg/l), the highest P content was in P5 (99.53 mg/l) and the highest K content was in P2 (12.59 mg/l). The N, P and K content in this fertilizer, however, is lower than the standard value SNI No.70/Permentan/SR 140/2011. Even though the growth of A. microphylla fertilized with the liquid fertilizer was slightly higher than the plant grown in the water, but it was significantly lower than that of the plant fertilized with chicken manure. This fact indicates that the quality of the liquid fertilizer made from tofu liquid waste was lower than the chicken manure fertilizer.Keyword: Tofu liquid waste, water hyacinth powde, Liquid Fertilizer, Azolla microphylla